2016
DOI: 10.1002/aenm.201600814
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Low‐Temperature Pseudodegradation of Photovoltaic Performance in Planar Perovskite Solar Cell by Optoelectronic Observation

Abstract: The time evolution of the current–voltage characteristic of planar heterojunction perovskite solar cell (PSC) is studied within an operating temperature range of 200–325 K. The photovoltaic (PV) performance of PSC is found to be influenced by five carrier transport pathways, which strongly depend on operating temperature and light illumination. At low temperature, a severe degradation of PV performance is presented but temporary. This is attributed to ion accumulation at the TiO2/CH3NH3PbI3 and hole transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
(85 reference statements)
1
21
0
Order By: Relevance
“…[25][26][27] Several studies indicated that, regardless of particular architecture and constituents within the PSCs, X defects migrate and reversibly accumulate within the perovskite lattice in narrow Debye layers at the interfaces with the charge selective contacts. 19,[28][29][30][31][32][33][34] Depending on voltage and light bias conditioning, accumulation of ions (and their vacancies) partially screens the built-in electric field and possibly creates interfacial electronic trap states, which reduce the charge extraction efficiency. 25,30,31,[34][35][36][37][38][39][40][41][42][43] Ion migration on timescales from 10 -1 to 10 2 s has been widely investigated to explain the hysteresis of current density-voltage (J-V) curves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Several studies indicated that, regardless of particular architecture and constituents within the PSCs, X defects migrate and reversibly accumulate within the perovskite lattice in narrow Debye layers at the interfaces with the charge selective contacts. 19,[28][29][30][31][32][33][34] Depending on voltage and light bias conditioning, accumulation of ions (and their vacancies) partially screens the built-in electric field and possibly creates interfacial electronic trap states, which reduce the charge extraction efficiency. 25,30,31,[34][35][36][37][38][39][40][41][42][43] Ion migration on timescales from 10 -1 to 10 2 s has been widely investigated to explain the hysteresis of current density-voltage (J-V) curves.…”
Section: Introductionmentioning
confidence: 99%
“…prolonged exposure to continuous light and voltage bias. 29,39,[50][51][52][53][54][55] In this work, we provide direct evidence of electric field-induced ion migration and its effects on the long-term performance of perovskite solar cells working under different loads.…”
Section: Introductionmentioning
confidence: 99%
“…There are a handful of reports showing decreased performance at low temperature. These weakening phenomena caused by lowering temperature are ascribed to many causes including frozen carrier diffusion [ 13 ], reduced absorption [ 14 ], interfacial ion accumulation [ 15 ], phase transition [ 16 ] and radiative [ 17 ] and nonradiative [ 18 ] recombination. However, there are also many reports that low-temperature operation is not a restriction but an enhancement to overall photoelectric performance, ranging from low-dimension materials to nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have dealt with the temperature and light intensity dependence separately. Many of the previous reports have primarily emphasized the impact on PSC performance at low temperatures and in phase transition regions, and those studies have been conducted on relatively unstable perovskite compositions (e.g., CH 3 NH 3 PbI 3 , or MAPbI 3 for short), while other relevant compositions are yet to be investigated in depth. ,, Moreover, theories about the mechanisms that drive PCE variations are still inadequate and open to debate.…”
Section: Introductionmentioning
confidence: 99%
“…In most conventional solar cell semiconductors, such as silicon, CIGS, and CdTe, the PV performance declines with increasing temperature, resulting in a negative temperature coefficient (TC) throughout the operating temperature range. , Temperature-dependence studies of PSCs based on MAPbI 3 absorbers reported a monotonic decrease in PCE and other PV parameters (i.e., open-circuit voltage ( V oc ), short-circuit current density ( J sc ), and fill factor (FF)) when the temperature was increased above RT . The degradation of organic-compound-based hole/electron transport materials, such as Spiro-OMeOTAD and Phenyl-C61-butyric acid methyl ester (PCBM), by pinhole formation and halide migration into the charge transport layers is reported as one of the main factors behind this decline. ,,,, A pseudo-degradation of PV performance and a slow photoresponse have been reported at low temperatures and attributed to charge accumulation at the transport layer/perovskite interface . Studies of MAPbI 3 over a wide range of temperature (−40 to 100 °C) have generally shown a significant decrease in performance at low and high temperatures, with a maximum PCE in the range 20–40 °C. , However, other studies have observed a steady improvement in PCE when the temperature was decreased from 25 to −20 °C .…”
Section: Introductionmentioning
confidence: 99%